Percutaneous Radiofrequency Ablation of the Posterior and Anterior Interosseous Nerves for Chronic Wrist Pain: A Novel Technique. Issue 2 (26th June 2021) - Smeraglia, Francesco; Berritto, Daniela; Basso, Morena A.; Mosillo, Giuseppe; Grassi, Roberto; Mariconda, Massimo
Abstract : The treatment of chronic wrist pain, due to posttraumatic, degenerative, or inflammatory arthritis, is challenging to adequately manage. The ideal surgical procedure should preserve wrist mobility and provide long-lasting pain relief. In this regard, denervation aims to decrease wrist pain by interrupting sensory innervation, without impairing motor function, and avoids the need for postoperative immobilization to decrease the risk of stiffness. For these reasons, denervation is particularly attractive as a possible treatment for chronic wrist pain. Our aim was to describe our novel technique for partial percutaneous wrist denervation, performed by radiofrequency ablation of the posterior and anterior interosseous nerves, and to report on the prospective outcomes over a 1-year follow-up for 3 patients (4 wrists) treated as of March 2019. The technique is performed on an outpatient basis and does not require postprocedure wrist immobilization or restriction in activities of daily living or work. Findings at the 1-year follow-up indicate that partial denervation improved grip strength, provided pain relief, maintained wrist motion, and improved subjective report of disabilities of the arm, shoulder, and hand. One patient did not report a benefit of the procedures, with other patients being very satisfied . Our percutaneous procedure is an evolution of the traditional partial denervation technique, providing advantages of being less invasive, not requiring restriction of movement or activities in the postoperative phase, can be performed on an out-patient basis, and does not preclude the subsequent use of invasive surgical procedures, as needed.